Preparation method of short-wave-pass ultraviolet optical filter
By plating multi-layer Ta2O5 and SiO2 film systems on the lens, combining vacuum coating technology and radio frequency ion source cleaning, the problem of insufficient transmittance control in the ultraviolet light segment to the visible light band is solved, and the problem of existing ultraviolet filters is not finely controlled from the ultraviolet light segment to the visible light band is realized. Optimization of high transmittance and cutoff effect.
Patent Information
- Application Number
- CN202411257988.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
AI Technical Summary
The transmittance control of existing ultraviolet filters from the ultraviolet to the visible light band is not fine enough, especially in the range of 360-460nm and the transmittance in the range of 530-560nm, which is difficult to meet certain applications. demand.
Using vacuum coating technology to plate 22 layers of Ta2O5 and SiO2 film systems on the first side of the lens, and 4 layers of Ta2O5 and SiO2 film systems on the second side, combining surface cleaning, temperature control and RF ion source cleaning to ensure The optical properties of the lens meet the requirements.
The average transmittance from the ultraviolet light segment to the visible light band is achieved in the range of 360-460nm and the average transmittance of the cut-off segment 530-560nm is less than 0.1%, which meets the high transmittance and Demand for cutoff effect.
Smart Images

Figure CN119265522A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of optical filters, and more specifically to a method for preparing a short-wave ultraviolet filter. Background Art
[0002] Optical filters are optical devices that can be used to select the desired radiation band. The function of optical filters is to selectively control the transmission of light of different wavelengths. They are widely used in life, including mobile phones, automotive electronics, medical imaging, sensors, audio-visual / digital electronic products, and many other fields.
[0003] Filters can generally be divided into ultraviolet filters, visible filters and infrared filters according to the spectral band. Ultraviolet filters can absorb visible light, allow ultraviolet light to pass through, and also allow some near-infrared light to pass through. Research and development of ultraviolet bandpass filters has been carried out in the industry, but further development is still needed. Summary of the invention
[0004] In view of the problems existing in the background technology, an object of the present invention is to provide a method for preparing a short-wave pass UV filter, which has an average transmittance of more than 98% in the transmission section 360-460nm from the ultraviolet light band to the visible light band at a test angle of 0°, and an average transmittance of less than 0.1% in the cut-off section 530-560nm.
[0005] Thus, a method for preparing a short-wave ultraviolet filter comprises the following steps: S1, cleaning the surface of a glass substrate product as a lens; S2, placing the treated lens into a fixture, and hanging the mounted lens into a vacuum coating machine cavity, wherein the temperature of the cavity is set to 150°C; S3, starting the vacuum coating machine to evacuate the vacuum to a degree of vacuum of 1.0×10 -3Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the RF ion source are: output ion acceleration voltage 750V, output ion current 750mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 75sccm; S4, coat the short-wave pass film system on the first side of the lens, the short-wave pass film system is 80.04H90.05L 75.25H 79.63L 66.91H 101.42L 52.56H 105.14L 59.19H92.56L 62.15H 98.59L55.4H 102.89L 58.89H 95.45L 63.02H 98.14L 60.9H107.93L 58.64H 55.22L, where H represents a Ta2O5 film layer with an optical thickness of λ0 / 4, L represents a SiO2 film layer with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, the numbers before H and L are the thickness of the film layer in nm, both Ta2O5 and SiO2 film layers are deposited by electron beam evaporation and assisted by radio frequency ion source evaporation, the deposition rate of Ta2O5 film layer is 0.4nm / s, and the deposition rate of SiO2 film layer is 1nm / s; S5, after the short-wave pass film system is deposited on the first side of the lens, wait for the cavity to cool to below 50-60°C and take out the fixture together with the product; S6, repeat steps S1 to S3; S7, deposit an anti-reflection film system on the second side of the lens, the anti-reflection film system is 16.53H 26.98L28.44H 76.55L, where H represents a Ta2O5 film with an optical thickness of λ0 / 4, L represents a SiO2 film with an optical thickness of λ0 / 4, λ0 is the wavelength of incident light, the numbers before H and L are the thickness of the film in nm, both Ta2O5 and SiO2 films are deposited by electron beam evaporation and assisted by a radio frequency ion source, the deposition rate of the Ta2O5 film is 0.4nm / s, and the deposition rate of the SiO2 film is 1nm / s; S8, after the anti-reflection film system is coated on the second side of the lens, wait for the cavity to cool to below 50-60°C before taking out the fixture together with the product.
[0006] The beneficial effects of the present disclosure are as follows: in the preparation method of the short-wave pass ultraviolet filter according to the present disclosure, through step S4 of coating a short-wave pass film system consisting of 22 layers of Ta2O5 and SiO2 on the first surface of the lens and step S7 of coating a reflective enhancement film system consisting of 4 layers of Ta2O5 and SiO2 on the second surface of the lens, and combined with the surface cleaning of steps S1 and S6, the cavity temperature of steps S2 and S6, the ion source cleaning of steps S3 and S6, and the cooling of steps S5 and S8, the average transmittance of the ultraviolet light band to the visible light band at a test angle of 0° in the transmission section 360-460nm is more than 98%, and the average transmittance of the cut-off section 530-560nm is less than 0.1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a curve diagram of the transmittance from the ultraviolet light band to the visible light band at a test angle of 0° in Example 1. DETAILED DESCRIPTION
[0008] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0009] [Preparation method of short-wave ultraviolet filter]
[0010] The method for preparing the short-wave pass ultraviolet filter according to the present disclosure comprises the steps of:
[0011] S1, cleaning the surface of a product serving as a glass substrate of a lens;
[0012] S2, put the processed lens into the fixture, and hang the mounted lens into the vacuum coating machine cavity, and the temperature of the cavity is set to 150℃;
[0013] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the RF ion source are: exit ion acceleration voltage 750V, exit ion current 750mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 75sccm;
[0014] S4, short wave pass film is coated on the first side of the lens, the short wave pass film is 80.04H 90.05L75.25H79.63L 66.91H 101.42L 52.56H 105.14L 59.19H 92.56L 62.15H 98.59L55.4H 102.89L58.89H 95.45L 63.02H 98.14L 60.9H 107.93L 58.64H 55.22L, H represents a Ta2O5 film with an optical thickness of λ0 / 4, L represents a SiO2 film with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, the numbers before H and L are the thickness of the film in nm, both Ta2O5 and SiO2 films are deposited by electron beam evaporation and assisted by radio frequency ion source, the deposition rate of Ta2O5 film is 0.4nm / s, and the deposition rate of SiO2 film is 1nm / s;
[0015] S5, after the short-wave pass coating system is coated on the first side of the lens, wait for the cavity to cool down to below 50-60°C and take out the fixture together with the product;
[0016] S6, repeating steps S1 to S3;
[0017] S7, anti-reflection film system is coated on the second surface of the lens, the anti-reflection film system is 16.53H 26.98L 28.44H76.55L, H represents a Ta2O5 film layer with an optical thickness of λ0 / 4, L represents a SiO2 film layer with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, the numbers before H and L are the thickness of the film layer in nm, the Ta2O5 and SiO2 film layers are both deposited by electron beam evaporation and assisted by radio frequency ion source evaporation, the deposition rate of the Ta2O5 film layer is 0.4nm / s, and the deposition rate of the SiO2 film layer is 1nm / s;
[0018] S8, after the anti-reflection coating system is coated on the second surface of the lens, wait for the cavity to cool down to below 50-60℃ and then take out the fixture together with the product.
[0019] In the preparation method of the short-wave pass ultraviolet filter according to the present disclosure, by step S4 of coating a short-wave pass film system consisting of 22 layers of Ta2O5 and SiO2 on the first surface of the lens and step S7 of coating a reflective enhancement film system consisting of 4 layers of Ta2O5 and SiO2 on the second surface of the lens, combined with the surface cleaning of steps S1 and S6, the cavity temperature of steps S2 and S6, the ion source cleaning of steps S3 and S6, and the cooling of steps S5 and S8, as verified in Example 1 of the test process described later, the average transmittance in the transmission section 360-460nm from the ultraviolet light band to the visible light band at a test angle of 0° is more than 98%, and the average transmittance in the cut-off section 530-560nm is less than 0.1%.
[0020] The surface cleaning of step S1 and step S6 is beneficial to improving the surface conditions of the first and second surfaces of the lens, and helps to improve the bonding performance between the short-wave pass film system on the first surface and the anti-reflection film system on the second surface and the corresponding surfaces of the lens. For example, the surface of the lens is cleaned by ultrasonic or hand wiping.
[0021] In one example, the glass substrate is K9 glass. For example, the thickness of the glass substrate is 1 mm.
[0022] The temperature setting of the vacuum coating machine in step S2 heats the lens through the cavity of the coating machine, which helps the growth of the Ta2O5 film from the lens and reduces the growth stress of Ta2O5.
[0023] Step S3 uses a radio frequency ion source for cleaning, which will remove impurities and oil molecules adsorbed on the surface of each surface of the lens, thereby greatly improving the interface state and helping to improve the bonding performance between the Ta2O5 film and the lens. At the same time, cleaning by a radio frequency ion source can heat each surface of the lens, which helps the growth of the Ta2O5 film from the lens and reduces the growth stress of the Ta2O5 film.
[0024] In one example, in step S4 and step S7, the parameters of the RF ion source used in coating the Ta2O5 film are: exit ion acceleration voltage 1150V, exit ion current 950mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm; the parameters of the RF ion source used in coating the SiO2 film are: exit ion acceleration voltage 900V, exit ion current 900mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm.
[0025] [test]
[0026] Example 1
[0027] The preparation method of the short wave pass UV filter adopts the following steps:
[0028] S1, using ultrasonic cleaning to clean the surface of a glass substrate product used as a lens, the glass substrate is K9 glass, and the thickness of the glass substrate is 1 mm;
[0029] S2, putting the processed lens into the fixture, and hanging the mounted lens into the cavity of the vacuum coating machine. The temperature of the cavity is set to 150°C. The vacuum coating machine is the Opto-Tech OTFC-1300 with a radio frequency ion source produced by Opto-Tech (Shanghai) Co., Ltd.;
[0030] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the RF ion source are: exit ion acceleration voltage 750V, exit ion current 750mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 75sccm;
[0031] S4, short wave pass film is coated on the first side of the lens, the short wave pass film is 80.04H 90.05L75.25H79.63L 66.91H 101.42L 52.56H 105.14L 59.19H 92.56L 62.15H 98.59L55.4H 102.89L58.89H 95.45L 63.02H 98.14L 60.9H 107.93L 58.64H 55.22L, H represents a Ta2O5 film with an optical thickness of λ0 / 4, L represents a SiO2 film with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, the numbers before H and L are the thickness of the film in nm, both Ta2O5 and SiO2 films are deposited by electron beam evaporation and assisted by radio frequency ion source, the deposition rate of Ta2O5 film is 0.4nm / s, and the deposition rate of SiO2 film is 1nm / s;
[0032] S5, after the short-wave pass coating system is coated on the first surface of the lens, wait for the cavity to cool to 60°C and take out the fixture together with the product;
[0033] S6, repeating steps S1 to S3;
[0034] S7, an antireflection film system is coated on the second surface of the lens. The antireflection film system is 16.53H 26.98L 28.44H76.55L, H represents a Ta2O5 film layer with an optical thickness of λ0 / 4, L represents a SiO2 film layer with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, and the numbers before H and L are the thickness of the film layer in nm. Both the Ta2O5 and SiO2 film layers are deposited by electron beam evaporation and assisted by a radio frequency ion source. The deposition rate of the Ta2O5 film layer is 0.4nm / s, and the deposition rate of the SiO2 film layer is 1nm / s;
[0035] S8, after the antireflection coating system is coated on the second surface of the lens, wait for the cavity to cool to 60°C and take out the fixture together with the product;
[0036] Among them, in step S4 and step S7,
[0037] The parameters of the radio frequency ion source used for coating the Ta2O5 film are: output ion acceleration voltage 1150V, output ion current 950mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm;
[0038] The parameters of the radio frequency ion source used in the deposition of the SiO2 film are: exit ion acceleration voltage 900 V, exit ion current 900 mA, grid ion deflection voltage 600 V, argon flow rate 8 sccm, oxygen flow rate 50 sccm.
[0039] Figure 1 It is a curve diagram of the transmittance from the ultraviolet light band to the visible light band when the test angle plating of Example 1 is 0°.
[0040] from Figure 1 It can be seen that when the test angle is 0°, the average transmittance in the transmission section 360-460nm from ultraviolet light to visible light is more than 98%, and the average transmittance in the cutoff section 530-560nm is less than 0.1%.
[0041] According to the content of GJB2485-95 General Specification for Optical Films, the overall performance of the product and the film systems on both sides are tested.
[0042] Water bubble test: The product prepared in Example 1, together with the short-wave pass film system on the first surface and the anti-reflection film system on the second surface, was subjected to a water bubble test with tap water for 10 minutes. It was found that the short-wave pass film system on the first surface and the anti-reflection film system on the second surface did not fall off the product, and there was no cracking of the short-wave pass film system on the first surface and the anti-reflection film system on the second surface.
[0043] Adhesion test: After the bubble test with tap water was completed, the shortwave pass film system on the first side of the product was pasted with 3M tape by hand and the tape was pulled in the direction opposite to the pasting end, but the shortwave pass film system was not pulled up; for the second side of the product, the anti-reflection film system on the second side of the product was pasted with 3M tape by hand and the tape was pulled in the direction opposite to the pasting end, but the anti-reflection film system was not pulled up.
[0044] The water bubble test and tape pulling test show that the shortwave pass film on the first surface and the anti-reflection film on the second surface of the product have good adhesion.
[0045] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for preparing a short-wave pass ultraviolet filter, characterized in that: Includes steps: S1, cleaning the surface of a product serving as a glass substrate of a lens; S2, put the processed lens into the fixture, and hang the mounted lens into the vacuum coating machine cavity, and the temperature of the cavity is set to 150℃; S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.0×10 -3 Pa, turn on the auxiliary coating RF ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the RF ion source are: exit ion acceleration voltage 750V, exit ion current 750mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 75sccm; S4, short wave pass film is coated on the first surface of the lens, the short wave pass film is 80.04H 90.05L75.25H 79.63L66.91H 101.42L 52.56H 105.14L 59.19H 92.56L 62.15H 98.59L55.4H 102.89L 58.89H95.45L 63.02H 98.14L 60.9H 107.93L 58.64H 55.22L, where H represents a Ta2O5 film with an optical thickness of λ0 / 4, L represents a SiO2 film with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, and the numbers before H and L are the thickness of the film in nm. Both the Ta2O5 and SiO2 films are deposited by electron beam evaporation and assisted by a radio frequency ion source. The deposition rate of the Ta2O5 film is 0.4nm / s, and the deposition rate of the SiO2 film is 1nm / s. S5, after the short-wave pass coating system is coated on the first side of the lens, wait for the cavity to cool down to below 50-60°C and take out the fixture together with the product; S6, repeating steps S1 to S3; S7, an antireflection film system is coated on the second surface of the lens. The antireflection film system is 16.53H 26.98L 28.44H76.55L, where H represents a Ta2O5 film layer with an optical thickness of λ0 / 4, L represents a SiO2 film layer with an optical thickness of λ0 / 4, λ0 is the wavelength of the incident light, and the numbers before H and L are the thickness of the film layer in nm. Both the Ta2O5 and SiO2 film layers are deposited by electron beam evaporation and assisted by a radio frequency ion source. The deposition rate of the Ta2O5 film layer is 0.4nm / s, and the deposition rate of the SiO2 film layer is 1nm / s; S8, after the anti-reflection coating system is coated on the second surface of the lens, wait for the cavity to cool down to below 50-60℃ and then take out the fixture together with the product.
2. The method for preparing a short-wave pass ultraviolet filter according to claim 1, characterized in that: In step S1, the surface of the lens is cleaned by ultrasonic wave or hand wiping.
3. The method for preparing a short-wave pass ultraviolet filter according to claim 1, characterized in that: The glass substrate is K9 glass.
4. The method for preparing a short-wave pass ultraviolet filter according to claim 3, characterized in that: The thickness of the glass substrate is 1 mm.
5. The method for preparing a short-wave pass ultraviolet filter according to claim 1, characterized in that: In step S4 and step S7, The parameters of the radio frequency ion source used for coating the Ta2O5 film are: output ion acceleration voltage 1150V, output ion current 950mA, grid ion deflection voltage 600V, argon flow rate 8sccm, oxygen flow rate 50sccm; The parameters of the radio frequency ion source used in the deposition of the SiO2 film are: exit ion acceleration voltage 900 V, exit ion current 900 mA, grid ion deflection voltage 600 V, argon flow rate 8 sccm, oxygen flow rate 50 sccm.
Citation Information
Cited By
High-transmittance film of laser, preparation method of high-transmittance film and high-power pulse laser
CN120914594A
High-transmittance ultraviolet short-wave pass filter and preparation method thereof
CN121386062A
High-transmittance ultraviolet short-wave pass filter and preparation method thereof
CN121386062B